I am large, I contain multitudes: lyric cohesion and conflict in Second Isaiah - Heffelfinger, Katie M. (Biblical interpretation series, 2011)
This thesis takes a lyric poetic approach by examining the series of poems on the homecoming to Zion as an element of comfort of the message of Second Isaiah. The practical application of this approach shows Second Isaiah to be characterized by tension, conflict, and juxtaposition as he addresses his audience with searing indictments in the 'book of comfort.' The return from exile is seen as a journey embedded within Israel's relationship with Yhwh, with Yhwh wavering between indignation and compassion, and finally deciding in favor of that relationship. This book highlights the tonalities of the divine voice as central to Second Isaiah's poetic mode of cohesion and essential to the conflicted comfort offered Zion